Seroprevalence of Toxoplasma gondii and Neospora caninum in camels recently imported to Egypt from Sudan and a global systematic review - Fereig, Ragab M.; Abdelbaky, Hanan H.; El-Alfy, El-Sayed; El-Diasty, Mohamed; Elsayed, Ahmed; Mahmoud, Hassan Y. A. H.; Ali, Alsagher O.; Ahmed, Abdulrahman; Mossaad, Ehab; Alsayeqh, Abdullah F.; Frey, Caroline F. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Toxoplasma gondii and Neospora caninum are closely related intracellular protozoan parasites of medical and veterinary concern by causing abortions and systemic illness. Limited or ambiguous data on the prevalence of T. gondii and N. caninum in camels triggered us to conduct this study. Methods Camels (n = 460) recently imported from Sudan and destined mainly for human consumption, were tested for specific antibodies against these protozoans using commercially available ELISAs. From the two only quarantine stations for camels from Sudan, 368 camels were sampled between November 2015 and March 2016 in Shalateen, Red Sea governorate, and 92 samples were collected between September 2018 and March 2021 from Abu Simbel, Aswan governorate. Results & Discussion Overall, seropositive rates in camels were 25.7%, 3.9% and 0.8% for T. gondii, N. caninum and mixed infection, respectively. However, marked differences were found between the two study sites and/or the two sampling periods: For T. gondii, a higher rate of infection was recorded in the Red Sea samples (31.5%, 116/368; odds ratio 20.7, 5.0-85.6; P<0.0001) than in those collected in Aswan (2.2%, 2/92). The opposite was found for N. caninum with a lower rate of infection in the Red Sea samples (0.82%, 3/368; odds ratio 23.7, 6.7-83.9; P<0.0001) than in the samples from Aswan (16.3%, 15/92). Additionally, our systematic review revealed that the overall published seroprevalence of T. gondii and N. caninum was 28.6% and 14.3% in camels worldwide, respectively. To the best of our knowledge, this study provides the first record of seroprevalence of both T. gondii and N. caninum in recently imported camels kept under quarantine conditions before delivery to other Egyptian cities and regions. In addition, our review provides inclusive data on the prevalence of T. gondii and N. caninum in camel globally. This knowledge provides basic data for the implementation of strategies and control measures against neosporosis and toxoplasmosis.